Beyond the surface: understanding dentine hypersensitivity through literature and expert opinion - Nehete, Swati; Prabhudesai, Sushrut; Satpathy, Anurag; Grewal, Mandeep; Tyagi, Ankita (International Journal Of Community Medicine And Public Health, 2025)
Dentine hypersensitivity (DH) is a prevalent condition marked by acute, transient pain resulting from exposed dentine, which can severely impact a patient’s quality of life and daily activities. The transient and often underreported nature of DH complicates both diagnosis and management. This expert opinion addresses current diagnostic and therapeutic approaches for DH, with a specific focus on practices within Indian clinical settings. Diagnosis necessitates a detailed patient history, clinical examination and the application of various stimuli to confirm hypersensitivity whilst excluding other dental pathologies. Enhanced diagnostic protocols and advancements in biomaterials are crucial for optimizing DH management and improving patient outcomes. The experts discussed current clinical practices and future directions in managing DH, with a focus on bioactive glasses like BioMin® that may be used to reduce tooth sensitivity and protect against tooth decay.